Cellulite and extracorporeal Shockwave therapy (CelluShock-2009) - a Randomized Trial - Joest Beatrice; Knobloch Karsten; Vogt Peter M (BMC, 2010)
Abstract Background Cellulite is a widespread problem involving females' buttocks and thighs based on the female specific anatomy. Given the higher number of fat cells stored in female fatty tissue in contrast to males, and the aging process of connective tissue leads to an imbalance between lipogenesis and lipolysis with subsequent large fat cells bulging the skin. In addition, microcirculatory changes have been suggested, however remain largely unknown in a controlled clinical setting. We hypothesize that the combination of extracorporeal shockwave and a daily gluteal muscle strength program is superior to the gluteal muscle strength program alone in cellulite. Methods/Design Study design: Randomized-controlled trial. IRB approval was granted at Hannover Medical School, Germany on May 22, 2009. For allocation of participants, a 1:1 ratio randomization was performed using opaque envelopes for the concealment of allocation. Reporting: according to CONSORT 2010. Eligible patients were females aged 18 or over and 65 or younger with cellulite with documented cellulite 1°-4° according to the Nürnberger score. Exclusion criteria were suspected or evident pregnancy, no cellulite, no informed consent or age under 18 years or above 65 years. Patients were recruited by advertisements in local regional newspapers and via the Internet. Analysis: Intention-to-treat. Outcome parameters: a) Photonumeric severity scale, b) Nürnberger Score, c) circumference measurements, d) capillary blood flow, e) tissue oxygen saturation, f) postcapillary venous blood flow. Intervention group: Six sessions of extracorporeal focused shock wave for six sessions (2000 impulses, 0,25 mJ/m2 every 1-2 weeks) at both gluteal and thigh regions plus a specific gluteal strength exercise training. Control group: Six sessions of sham extracorporeal focused shock wave for six sessions (2000 impulses, 0,01 mJ/m2 every 1-2 weeks) at both gluteal and thigh regions plus a specific gluteal strength exercise training. Follow-up: 12 weeks. Blinding was achieved for all participants enrolled in the trial, the photograph taking the digital images for the primary outcome measure, the two assessors of the outcome measures, all additional health care providers and for the analyst from the biometrical department. Only one researcher (BJ) was aware of the group assignment performing the randomisation and the extracorporeal shock wave therapy. Discussion This randomised-controlled trial will provide much needed evidence on the clinical effectiveness of focused extracorporal shock wave therapy as an adjunct to gluteal strength training in females suffering cellulite. ClinicalTrials.gov identifier NCT00947414